2008
DOI: 10.1016/j.bbamcr.2008.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage mediated protein hydroperoxide formation and lipid oxidation in low density lipoprotein are inhibited by the inflammation marker 7,8-dihydroneopterin

Abstract: The formation of oxidised low density lipoprotein (LDL) within the atherosclerotic plaque appears to be a factor in the development of advanced atherosclerotic plaques. LDL oxidation is dependent on the balance of oxidants and antioxidants within the intima. In addition to producing various oxidants, human macrophages release 7,8-dihydroneopterin which in vivo is oxidised to the inflammation marker neopterin. Using macrophage-like THP-1 cells and human monocyte-derived macrophages, we demonstrate that 7,8-dihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Absorption bands from 2800-3000 cm -1 corresponding to methyl groups are well defined, no matter the type of the sample, either free or deposed LDL. As observable from figures 5 and 6, the amide specific band absorptions for proteins, amide I band around 1654 cm -1 and amide II band around 1541 cm -1 (Firth et al 2008;Banuelos et al 1995) are not changed when LDL was deposited on the gold support. This observation is important because it proved that the secondary structure of protein is preserved subsequent deposition therefore it can be concluded that the deposition on solid support did not affect theLDL functionality, and, consequently, that deposed LDL is expected to react with free radicals according to the same pathway as free LDL.…”
Section: Ftir Assessment Of Native and Oxidised Low-density Lipoproteinmentioning
confidence: 62%
“…Absorption bands from 2800-3000 cm -1 corresponding to methyl groups are well defined, no matter the type of the sample, either free or deposed LDL. As observable from figures 5 and 6, the amide specific band absorptions for proteins, amide I band around 1654 cm -1 and amide II band around 1541 cm -1 (Firth et al 2008;Banuelos et al 1995) are not changed when LDL was deposited on the gold support. This observation is important because it proved that the secondary structure of protein is preserved subsequent deposition therefore it can be concluded that the deposition on solid support did not affect theLDL functionality, and, consequently, that deposed LDL is expected to react with free radicals according to the same pathway as free LDL.…”
Section: Ftir Assessment Of Native and Oxidised Low-density Lipoproteinmentioning
confidence: 62%
“…The exact identity of these is however less clear, and quantification can be problematic due to the ready decomposition or reaction of these species. Exposure of isolated low-density lipoproteins to O 2 −• generating systems [ 180 ] or human macrophage-like THP-1 cells has been reported to yield hydroperoxides on the apolipoprotein B100 protein, as well as lipid hydroperoxides [ 181 ]. The formation of these species was inhibited by the radical-scavenging antioxidant 7,8-dihydroneopterin [ 181 ].…”
Section: Evidence For Amino Acid- Peptide- and Protein-hydroperoxidementioning
confidence: 99%
“…Immune staining of carotid plaque has shown regions with high levels of neopterin associated with macrophages [7,9]. Our previous analysis of atherosclerotic plaques removed from carotid arteries showed neopterin concentrations ranging from 0.72 to 2.34 μmol/L within the whole plaque [15]. Within one individual plaque that we sectioned, we reported large variations in neopterin concentration ranging from 0.4 to 2.2 nmol/g of wet tissue [6].…”
Section: Introductionmentioning
confidence: 94%
“…Neopterin causes significant cellular stress at elevated concentrations [10][11][12], while 7,8-dihydroneopterin has been shown to be a potent antioxidant capable of inhibiting copper, peroxyl radical and cell-mediated oxidisation of low-density lipoprotein (LDL) [13][14][15]. Macrophage uptake of oxidised LDL (oxLDL) is decreased by 7,8-dihydroneopterin-mediated down-regulation of the CD36 scavenger receptor [16].…”
Section: Introductionmentioning
confidence: 99%